Expert system for coffee rust detection based on supervised learning and graph pattern matching. (2017) - Lasso, Emmanuel; Thamada, Thiago Toshiyuki; Meira, Carlos Alberto Alves; Corrales, Juan Carlos
Diseases in agricultural production systems represent one of the main reasons of losses and poor-quality products. For coffee production, experts in this area suggest that weather conditions and crop physical properties are the main variables that determine the development of coffee rust. This paper proposes an extraction of rules to detect coffee rust from induction of decision trees and expert knowledge. In order to obtain a model with greater expressiveness and interpretability, a graph-based representation is proposed. Finally, the extracted rules are evaluated using an expert system supported on graph pattern matching.